Nilai-Nilai Transendental dalam Cerita Rakyat Kabupaten Keerom, Papua: Watuwe dan Towyatuwa - Ummu Fatimah Ria Lestari (Balai Bahasa Provinsi Papua, 2019)
This paper purposes to explain transcendental value in Watuwe and Towyatuwa is a folklore of Keerom. The result of this analysis found the values as follows: (1) animism and dynamism belief, (2) human limitedness, (3) mystic, irrational, and supernatural power, and (4) good attitudes, patience and effort for the glorify process.